Cropping Patterns in the South East Coastal Region of Bangladesh - Shahidullah, SM; Talukder, MSA; Kabir, MS; Khan, AH; Elahi, Nur-E (Journal of Agriculture & Rural Development, 2008)
The study was conducted in greater Noakhali district to investigate the major cropping patterns during 20002001. Information was collected through a structured interview schedule. A total of 18 major cropping patterns were identified. Most dominant cropping pattern, single T. Aman alone occupied 35% land of net cropped area. The next three, BoroFallowT. Aman, FallowB.AusT. Aman and single Boro represents 14, 11 and 11%, respectively of the net cropped area. A sharp variation was observed in cropping patterns among the different upazillas. Crop land of Noakhali, Companiganj, and Ramgati is mainly occupied by single T. Aman cropping pattern. Lion share of net cropped area in Feni, Chhagalnaiya, Parshuram and Raipur is covered by BoroFallowT. Aman pattern. Begumganj and Chatkhil are an exception. More than 80% of the cropped area is in these two upazillas is cahracterized by single Boro cropping pattern. The average cropping intensity of the greater Noakhali district was 163%. The highest cropping intensity was 194% in Ramganj and the lowest 115 % was in Begumganj. The highest adoption rate of modern rice varieties was found in BoroFallowT. Aman cropping pattern in all upazillas. The farmers need improved varieties of Aus, T. Aman and minor Rabi crops purposively suitable for coastal area. Researches in these fields should get priority. Single Boro area, especially of Begumganj and Chatkhil is the most potential area for fish culture after the harvest of Boro rice. Key words: Cropping patterns, cropping intensity, coastal area.